Conflict Archaeology as a Source of Local History Education: Potential and Challenges in The City of Palopo - Benyamin Lufpi (Riviera Publishing, 2026)
Palopo City was once the seat of the Luwu Kingdom and retains conflict archaeology remains from several historical periods, ranging from internal succession conflicts and Islamization to colonial contestation and post-independence resistance. This study aims to identify these conflict archaeology remains and to analyze the potential and challenges of utilizing them as sources for local history education. A qualitative descriptive approach was used, combining archaeological methods (observation, description, contextual analysis) with historical methods (source criticism, explanation, historiography), with data collected through field observation, literature review, and interviews with ten informants comprising three History/Social Studies teachers, two Museum Batara Guru curators, one caretaker of the Lokkoe Royal Tomb Complex, one administrator of the Jami' Tua Mosque of Palopo, and two representatives from the Palopo City Cultural Affairs and Education Offices. The findings identify four categories of conflict archaeology remains and confirm through interview data that while the first three site categories have been mentioned in classroom instruction as local content and visited through Education Office programs, their utilization remains unsystematic, dependent on individual teacher initiative, and constrained by scheduling, permits, and sensitivity of certain narratives. Each category holds significant educational potential that remains underutilized, while facing specific challenges related to site sanctity, accessibility, narrative complexity, and the scarcity of primary sources. The study recommends differentiated utilization strategies and cross-sector coordination among site managers, the cultural affairs office, and the education office, anchored in Palopo City Regional Regulation Number 8 of 2014.